2015
DOI: 10.1088/0004-637x/812/2/139
|View full text |Cite
|
Sign up to set email alerts
|

SIXTEEN YEARS OFULYSSESINTERSTELLAR DUST MEASUREMENTS IN THE SOLAR SYSTEM. I. MASS DISTRIBUTION AND GAS-TO-DUST MASS RATIO

Abstract: In the early 1990s, contemporary interstellar dust penetrating deep into the heliosphere was identified with the in-situ dust detector on board the Ulysses spacecraft. Between 1992 and the end of 2007 Ulysses monitored the interstellar dust stream. The interstellar grains act as tracers of the physical conditions in the local interstellar medium surrounding our solar system.Earlier analyses of the Ulysses interstellar dust data measured between 1992 and 1998 implied the existence of a population of 'big' inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 101 publications
3
58
0
1
Order By: Relevance
“…This result is consistent with the result of Krüger et al (2015), who detected an enhanced concentration of large (more than 1 microns) grains in the interstellar dust flow entering the Solar system precisely from the northern Galactic hemisphere together with the flow of neutral hydrogen and helium based on data from the dust detector onboard the Ulysses spacecraft. Moreover, the Galactic coordinates of the entry point of this flow into the Solar system (near l = 3…”
Section: Branch Giants Closer Than 700 Pcsupporting
confidence: 92%
“…This result is consistent with the result of Krüger et al (2015), who detected an enhanced concentration of large (more than 1 microns) grains in the interstellar dust flow entering the Solar system precisely from the northern Galactic hemisphere together with the flow of neutral hydrogen and helium based on data from the dust detector onboard the Ulysses spacecraft. Moreover, the Galactic coordinates of the entry point of this flow into the Solar system (near l = 3…”
Section: Branch Giants Closer Than 700 Pcsupporting
confidence: 92%
“…In addition, the size distributions of the polarizing grains are poorly known. In situ measurements of interstellar dust grains by Ulysses and other spacecraft show that the size range extends from ∼0.04 to 2.0 μm if the grains are compact silicates (Frisch et al 1999;Landgraf et al 2000;Krueger et al 2015;Sterken et al 2015). Since the wavelength of maximum polarization strengths depend on grain sizes, composition, and porosity (Serkowski et al 1975;Andersson & Potter 2006;Andersson 2015), the polarization strengths can not be compared because of the different spectral bands of the various data sets.…”
Section: Polarization Data Used To Determine the Magnetic Field Direcmentioning
confidence: 99%
“…The corresponding grains mass ranges are, roughly, M > 10 −14 kg for β ≤ 0.2, 10 −16 kg < M < 10 −14 kg for 0.2 < β < 1 and 5·10 −17 kg < M < 10 −16 kg for β > 1. Finally, to provide an upper value for the kinetic energy flux of impactors described by their β value, we have done the following simplification, which we believe is sufficient for the purpose of this study: Considering the ISD mass distribution and flux values reported by (Krüger et al, ), we apply a flux of 5·10 −5 m −2 /s to the particles with β = 1.3, 10 −5 m −2 /s to the particles with β = 1 and 10 −6 m −2 /s to the particles with β = 0.2.…”
Section: Interplanetary Dust Impactors: Methods and Simulation Resultsmentioning
confidence: 99%